Aksen dalam Interaksi Media YouTube ‘Curhat Bang’: Studi Sosiolinguistik terhadap Respons Audiens - Ardy, Zarin Agusti (Program Studi Magister Linguistik Terapan UNJ, 2025)
This article explores how regional accents in digital communication function as forms of symbolic legitimacy and resistance to the dominance of standardized language. The study analyzes two episodes from the YouTube channel Curhat Bang, featuring speakers with Kerinci and Javanese-Betawi accents recounting their traumatic experiences. Employing a critical sociolinguistic approach, this study draws on Pierre Bourdieu’s theory of symbolic power and Lippi-Green’s concept of language ideology. The method used is thematic content analysis of video transcripts and audience comments. The findings reveal that spontaneous speech, local dialects, and non-standard sentence structures are publicly perceived as indicators of honesty, authentic trauma, and narrative credibility. Audience responses not only embrace accent diversity but also affirm regional speech as authentic expression and a vehicle for social solidarity. These results demonstrate that digital media enables resistance to dominant language ideologies and fosters a shift in symbolic value within public communication practices. Accents once considered inferior are now perceived as voices of truth.